Prescribing Antibiotics Among Post-operative Patients in Obstetrics and Gynecology Department of Two Tertiary Care Hospitals of Bangladesh (Journal of Rangpur Medical College, 2026)
Background: Antibiotics are important in obstetrics and gynecology for preventing and treating infections, inappropriate use contributes to antimicrobial resistance. Objective: To evaluate the prescribing pattern of the antibiotics in postoperative patients admitted in gynaecology and obstetrics at Dhaka Medical College Hospital (DMCH) and Rangpur Medical College Hospital (RpMCH). Methods: This cross-sectional observational study was carried out among the post-operative patients admitted in Obstetrics and Gynecology Departments of Dhaka Medical College Hospital & Rangpur Medical College Hospital from July 2017 to June, 2018. A total of 500 sample; 250 from Dhaka center (DMCH) and 250 from Rangpur center (RpMCH), was enrolled through purposive sampling. Sociodemographic data of the participants, diagnosis, number of prescriptions containing antibiotic, numberof antibiotic per prescription, name of drugs in generic or in trade name were recorded. Results: Among 500 subjects, 250 were from gynaecological cases and 250 from obstetrical cases. The average age was29.88±11.29 years (range: 18-70 years), with most participants (56.6%) from rural areas. Among 3978 prescribed drugs, average number of drugs per prescription was 7.91±1.49 with 28.43 % being antibiotics. 34.23% drugs were prescribed by generic names and hospital supplied drugs were 39.64%. After surgery, 72.6% of patients received two injectable antibiotics, with higher rates in Dhaka (77.2%) compared to Rangpur (68%). The average number of injectable antibiotics was similar in both centers (2.17±0.48), but oral antibiotics were more common in Dhaka (2.22±0.48 vs 2.03±0.8). Most used injectable antibiotic was ceftriaxone (Dhaka center vs Rangpur center, 88.8%, vs 82.4%) and metronidazole (Dhaka center vs Rangpur center 95.2% vs 55.6%), while cefixime(Dhaka center vs Rangpur center 64% vs 44.4%) and metronidazole (Dhaka center vs Rangpur center 82.8% vs 22.8%) were the most common oral antibiotics at discharge. Conclusion: Ceftriaxone and Metronidazole were frequently administered to postoperative patients. This indicates a trend of polypharmacy that could be reduced by selecting broad-spectrum antibiotics after culture and sensitivity.J Rang Med Col.2026 Mar;11(1): 85-91